Suppression of liquid metal embrittlement in resistance spot welding of TRIP steel. (18th August 2019) - He, L.; DiGiovanni, C.; Han, X.; Mehling, C.; Wintjes, E.; Biro, E.; Zhou, N.Y.
ABSTRACT: Third-generation advanced high strength steels are typically given a zinc coating that provides excellent resistance to corrosion. During the resistance spot welding process, the melted zinc coating enables liquid metal embrittlement (LME) that causes cracking in the weld indent. In this study, LME in TRIP 1100 and TRIP 1200 steels was suppressed by placing aluminium interlayers added between the electrode and steel contact surface. Compared to welds exhibiting LME, TRIP 1100 with aluminium interlayers showed complete strength recovery while TRIP 1200 with aluminium interlayers resulted in a recovery of strength by 90%. Aluminium interlayers suppress LME by the formation of iron aluminides that hinder liquid zinc from coming in contact with the steel substrate, thus preventing LME.